Oscope identifies oscillatory genes in unsynchronized single cell RNA-seq experiments - Leng, Ning (Nat Methods, 2015)
Oscillatory gene expression is fundamental to mammalian development, but technologies to monitor expression oscillations are limited. We have developed a statistical approach called Oscope to identify and characterize the transcriptional dynamics of oscillating genes in single-cell RNA-seq data from an unsynchronized cell population. Applications to a number of data sets demonstrate the utility of the approach and also identify a potential artifact in the Fluidigm C1 platform.